2014
DOI: 10.1155/2014/279389
|View full text |Cite|
|
Sign up to set email alerts
|

Gitelman Syndrome in a School Boy Who Presented with Generalized Convulsion and Had a R642H/R642W Mutation in theSLC12A3Gene

Abstract: An 8-year-old Japanese boy presented with a generalized convulsion. He had hypokalemia (serum K 2.4 mEq/L), hypomagnesemia, and metabolic alkalosis (BE 5.7 mmol/L). In addition, his plasma renin activity was elevated. He was tentatively diagnosed with epilepsy on the basis of the electroencephalogram findings and was treated by potassium L-aspartate and carbamazepine to control the hypokalemia and seizure, respectively. However, a year later, the patient continued to have similar abnormal laboratory data. A pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Makino, et al reported the case of a school boy who initially presented with a generalized convulsion that the patient has persistent hypokalemia and metabolic alkalosis. They confirmed that the patient actually had GS, based on the two mutations of the SLC12A3 gen and they claimed that a patient showing persistent hypokalemia and metabolic alkalosis should be tested for GS and, if possible, diagnosed at the genetic level, even if the patient exhibits atypical clinical symptoms [10].…”
Section: Case Reportmentioning
confidence: 90%
“…Makino, et al reported the case of a school boy who initially presented with a generalized convulsion that the patient has persistent hypokalemia and metabolic alkalosis. They confirmed that the patient actually had GS, based on the two mutations of the SLC12A3 gen and they claimed that a patient showing persistent hypokalemia and metabolic alkalosis should be tested for GS and, if possible, diagnosed at the genetic level, even if the patient exhibits atypical clinical symptoms [10].…”
Section: Case Reportmentioning
confidence: 90%
“…Notably, certain individuals may remain asymptomatic, often leading to misdiagnoses as sporadic hypokalemia or hypomagnesemia. [ 3 ] Nonetheless, Severe adverse events have also been reported in the literature, encompassing growth retardation, [ 2 , 4 ] chondrocalcinosis, [ 5 ] generalized seizures, [ 6 , 7 ] non-periodic paralysis, [ 2 ] rhabdomyolysis, [ 8 ] and even cardiac arrest. [ 9 ] The course of GS typically follows a mild trajectory, characterized by predominantly modest clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences were aligned to human reference genome hg19 using the Burrows-Wheeler Aligner[13]. The duplicate reads were removed by the Samblaster[14]. The INDEL was re-aligned using GATK realignment and base quality score recalibration was performed.…”
Section: Case Presentationmentioning
confidence: 99%